IMPLEMENTATION OF COMMUNICATIVE STRATEGY OF DISCREDITATION AND ATTACK IN SPANISH POLITICAL DISCOURSE - Кучинська , Валерія (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article examines speech and language ways of expressing one of the main communicative and pragmatic strategies characteristic of political discourse - the strategy of discrediting the opponent. The research is based on the material of the speeches of the figures of the Spanish political space. The article examines the speeches of the leaders of competing political forces and analyzes the revealed linguistic features of the discrediting strategy and a number of tactics for its implementation. The strategy of discrediting and attacking the opponent is one of the most used and vividly presented in political discourse, which is explained by its effectiveness, since its use allows the speaker to simultaneously attack the authority of the opponent and raise authority of their own. Special attention was paid to negatively marked lexical units as the main means of expressing the considered strategy. Attention is also paid to features at other linguistic levels, in particular grammatical. Definitions of communicative strategies and tactics, the importance of their application for political discourse, examples of implementation of the discrediting strategy in Spanish-language political discourse are considered in the work. The tactic of verbal insinuation was singled out as the most vividly represented in the sample of examples for the study. __________ References: • Bacevich, F. S. Osnovi komunіkativnoї lіngvіstiki (Kiїv: Akademіja, 2009), 376. • Bєlova, A. D. «Komunіkativnі strategії і taktiki: problemi sistematiki.» Movnі і konceptual’nі kartini svіtu 10 (2004): 11–16. • Dan’shina, E. V. «Strategii i taktiki amerikanskogo predvybornogo diskursa.» Vіsnik Sums’kogo derzhavnogo unіversitetu. Serіja Fіlologіja 1 (2) (2007): 24–28. • Monastir’ova, L. «Diskursivna osobistіst’ u suchasnіj lіngvіsticі.» Naukovij vіsnik Mіzhnarodnogo gumanіtarnogo unіversitetu. Serіja «Fіlologіja» 39 (Odesa: Mіzhnarodnij gumanіtarnij unіversitet, 2019): 45–47. • Monastir’ova, L. «Komunіkativnі strategії perekonannja, jak odna z harakteristik movnoї osobistostі advokata (na materіalі hudozhnіh fіl’mіv SShA).» Fіlologіja. Socіal’nі komunіkacії26 (65), № 4, ch. 2 (2013): 305–310. • Monastir’ova, L. «Komunіkativnі strategії perekonannja jak odna z harakteristik movnoї osobistostі lіdera.» Vchenі zapiski TNU іmenі V. І. Vernads’kogo. Serіja: Fіlologіja. Socіal’nі komunіkacії 4 (2020): 176–180. • Pavluc’ka, V. A. «Polіtichnij diskurs: osoblivostі ta funkcії.» Vіsnik Zhitomirs’kogo derzhavnogo universitetu 3 (2008): 220–221. • Pragmatichnі ustanovki polіtichnogo diskursu ta sposobi їh realіzacії (na materіalі publіchnih vistupіv britans’kih polіtikіv), https://studfile.net/preview/ 9932178/. • Точицкая,Н. А. «Коммуникативные стратегии и тактики речевого воздействия в жанрах арт-журналистики (рецензия, репортаж).» Медиалингвистика 8 (3) (2021): 287–298. • Calderón, L. «Estrategias Aplicadas en Discursos Políticos del Socialismo del Siglo XXI.» Perspectivas Revista de Ciencias Sociales 3 (5) (2018): 112–130. • Chilton,Paul y Christina, Schäffner. Politics as Text and Talk. Analytic approaches to political discourse (Amsterdan / Philadelphia: John Benjamins Publishing Company, 2002). • Fernández Ulloa, T. y López Ruiz, M. C. «La argumentación en los discursos de Pedro Sánchez y Pablo Casado en el debate de investidura.» (España, 4 de enero de 2020). Círculo de Lingüística Aplicada a la Comunicación86 (2020): 199–212. • Gutiérrez, S. Discurso politico y argumentacion (2006): 1–11. • Komorowska, A. «Pragmática del discurso electoral y el uso de nosotros.» Études sur le texte dédiées à Halina Grzmil-Tylutki (2016): 121–134. • Ruiz, «Una cala en el lenguaje político español: análisis lingüístico de un discurso parlamentario.» Cauce, Revista Internacional de Filología y su Didáctica31 (2008): 141–160. • Schudson, «Sending a political message: lessons from the American 1790s.» Media, Culture and Society19 (3) (1997): 311–330. • Discurso de Pablo Casado (04.01.2020), https://www.youtube.com/watch?v= fbJyLjdFDVs (Дата звернення 19.09.2022). • Discurso de Pablo Iglesias (14.06.2017) https://www.youtube.com/watch?v= CFGLITa5jME (Дата звернення 20.09.2022). • Discurso de Pablo Iglesias (04.01.2020), https://www.youtube.com/watch?v=mw-B0CH2wEM (Дата звернення 20.09.2022). • Discurso de Pablo Iglesias (30.06.2020), https://www.youtube.com/watch?v= _GZEBacX_-8 (Дата звернення 20.09.2022). • Discurso de Santiago Abascal (08.06.2022), https://www.youtube.com/watch?v= X1dznm90PkE (Дата звернення 20.09.2022). • Discurso de Santiago Abascal (14.09.2022), https://www.youtube.com/watch?v= 4cDuXjDe12M (Дата звернення 23.09.2022). • Discursos de Pedro Sanchez y Alberto Núñez Feijóo (07.06.2022), https://www.youtube.com/watch?v=P_rmYGWl2nY (Дата звернення 28.09.2022).